Experimental study of petrophysical properties of a tight formation by considering the clay minerals and flow sensitivities (2016)
Quantitative X-ray diffraction analysis of rock, X-ray diffraction analysis of clay minerals types and components, Field Emission Scanning Electron Microscope (FESEM) and sensitivity flow experiments methods were used toresearch the effects of clay minerals on the porosity and permeability of Ordos Basin’s tight Chang 7 reservoir (Zhenbei area). These methods were also used to analyze the type, degree, and factors affecting reservoir sensitivity. The research showed that the reservoir possessed poor water, salt, and alkali sensitivity, poor to strong acid sensitivity and none to poor velocity sensitivity. Acid sensitivity among them had comparatively large differences, mainly because acid sensitivity was not only affected by chlorite but also by components of carbonate minerals. Stress sensitivity experiment results showed that the maximum degree of permeability damage in the rocks of this reservoir was median to very strong; irreversible damage level was weak to strong. Consequently, the experimental studies are favorable to not only determine the factor dominating the petrophysical properties of the tight formation, but also to optimize the follow-up development strategies, e.g. injection schedule and hydraulic fracturing implement. Estudio Experimental de las propiedades petrofísicas de una formación compacta al considerar las arcillas minerales y las respuestas de flujo ResumenEste trabajo utilizó análisis cuantitativos de rocas por difracción de rayos X, análisis de los tipos y componentes de arcillas minerales por difracción de rayos X, análisis con el microscopio electrónico de efecto de campo (FESEM, del inglés Field Emission Scanning Electron Microscope) y ensayos de respuesta de flujo para investigar los efectos de las arcillas minerales en la porosidad y permeabilidad del depósito Chang 7, en la cuenca del Ordos (región Zhenbei). Estos métodos también se utilizaron para analizar el tipo, el grado y los factores que afectan la respuesta del depósito. La investigación demuestra que el depósito posee poca agua, sal y respuesta alcalina, baja a fuerte respuesta de acidez, y ninguna a baja respuesta de velocidad. Entre estas características, la respuesta de acidez presentó grandes diferencias comparativas debido a que está afectada tanto por el clorito como por los componentes de minerales carbonatos. Los resultados de los ensayos de respuesta de tensión muestran que el máximo grado de daño por permeabilidad en las rocas del depósito es de mediano a muy fuerte; el nivel de daño irreversible va de débil hasta fuerte. Por lo tanto lo estudios experimentales son favorables no solo para determinar el factor dominante en las propiedades petrofísicas de la formación compacta sino también para optimizar las futuras estrategias de desarrollo, como una programación de las tareas de inyección y la implementación de la fractura hidráulica.